IMPLEMENTASI SUPPLY CHAIN MANAGEMENT UNTUK PRODUKSI PENGOLAHAN BAKSO CETAK PADA UD. BU GADIS - Ainun Mardiah; Jhonson Efendi Hutagalung; Febri Dristyan (LPPM STMIK Royal Kisaran, 2022)
Abstract: This research was conducted at a Home Industry company engaged in heavy food, namely printed meatballs. This study aims to apply the Supply Chain Management method for the production of printed meatball processing at UD. Mrs. Girl, to find out the problems that occurred, how to overcome the difficulties in obtaining information about the procurement of raw material stocks, which resulted in a shortage of raw materials in the production of printed meatball processing, and resulted in an imbalance between the stock of raw materials and the number of requests from consumers. So from these problems it is necessary to design a Supply Chain Management (SCM) application which aims to make it easier to manage the procurement of raw material stocks properly. The design tools used are (UML) Unified Modeling Language which will be designed using PHP and MySQL as databases. Keywords : Supply Chain Management; Printed Meatball Processing Production; PHP and MySQL. Abstrak: Penelitian ini dilakukan pada sebuah perusahaan Home Industry yang bergerak dibidang makanan berat, yaitu bakso cetak. Penelitian ini bertujuan untuk menerapkan metode Supply Chain Management untuk produksi pengolahan bakso cetak pada UD. Bu Gadis, untuk mengetahui permasalahan yang terjadi, bagaimana cara mengatasi kesulitan dalam mendapatkan informasi seputar pengadaan stok bahan baku, yang mengakibatkan kekurangan bahan baku dalam melakukan produksi pengolahan bakso cetak, dan mengakibatkan ketidakseimbangan antara stok bahan baku dengan jumlah permintaan dari pelanggan. Maka dari permasalahan tersebut diperlukan adanya perancangan aplikasi Supply Chain Management (SCM) yang bertujuan untuk memudahkan dalam mengatur pengadaan stok bahan baku dengan baik. Tools perancangan yang digunakan yaitu (UML) Unified Modeling Language yang akan dirancang dengan menggunakan PHP dan MySQL sebagai database. Kata Kunci: Supply Chain Management; Produksi pengolahan bakso cetak; PHP dan MySQL.